ANALISIS PENGARUH PEMASANGAN KAPASITOR SERI DAN RANGKAIAN PENYEARAH PADA PEMBEBANAN RESISTIF GENERATOR SINKRON MAGNET PERMANEN FLUKS AKSIAL PUTARAN RENDAH - , EMIR EL FIQHAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Recently, there are many developments in electric power generator research in Indonesia. But, the interest of environmental friendly electric power generation is still scarce. This study was conducted to resolve the problem electrical energy crisis by developing a small-size generators using permanent magnets Neodymium Ferrite Boron (NdFeB), which can be utilized as an alternative energy source by utilizing wind or micro-hydro energy in rural area. In the past researches, there are still constraint about the amount of voltage drop on the design of Axial Flux Permanent Magnet Synchronous Generator, which is has low speed with double rotor and single stator. Moreover, the voltage instability when the prime mover is a windmill also the focus on this research. The installation of serial capacitors and the rectifier installation is the right solution to overcome the existing problems. The test results obtained by that generator capable of generating electricity 50 Hz at 250 rpm and generates voltage of each phase R, S, and T, respectively for 18.25, 18.15, and 18.66 volt and the line voltage is 29,33